Revisiting the endemic Eugenia grandifolia (Myrtaceae), a rare species from the Brazilian state of Rio de Janeiro: extended description and conservation - Fernandes, Thiago; Braga, João Marcelo Alvarenga; Valdemarin, Karinne Sampaio; Denardi, Vinícius Luvizotto; Prieto, Pablo Viany; Mazine, Fiorella F. (Phytotaxa, 2025)
This paper documents the rediscovery of Eugenia grandifolia, an endemic species from the Brazilian state of Rio de Janeiro that was primarily known from 19th century collections. Eugenia grandifolia is remarkable by its relatively large, subsessile leaves with cordate bases, inflorescences in racemes and often ramiflorous, and fruits with up to seven seeds. We provide herein a second step lectotypification, updated morphological description, notes on taxonomy, distribution, habitat, and phenology of the species. The presence of colleters in the species is first recorded here. Its fruits, previously unknown to science, are illustrated and described herein, and the first photographic documentation of the live plant in its habitat is also presented. Finally, we present a distribution map and a reassessment of the conservation status of E. grandifolia.